PERBANDINGAN UNSUR-UNSUR DEUX EX MACHINA DALAM “PAK BELALANG” DAN “RUMPERLSTILTSKIN” - Syam, Essy (Jurnal Ilmu Budaya, 2017)
This writing compares elements of deux ex machina in two folklores entitle “Pak Belalang” and “ Rumpelstiltskin.” Thus, the objective of the research is to describe and to analyze the similarities and differences of the elements of deux ex machina used by eastern and western texts. To reach the aim, this analysis uses comparative analysis to compare the two folklores. Related to that, this analysis applies descriptive analysis in which the result of the analysis will be described clearly. From the description, it will show how the eastern and western’s texts use deux ex machina as one of the elements of conflict which varies the text.